Ketimpangan hukum dalam penanganan korupsi - latifah, nurul (Maliki Interdisciplinary Journal, 2025)
This study examines the weaknesses of law enforcers in overcoming corruption in Indonesia. The goal is to find out the very basic causative factors for the ineffective behavior of law enforcement officials and provide strategies for more effective improvement. This study uses a literature review method. This method is a combination of several relevant articles, journals, and websites from various sources to gain a deeper understanding related to the understanding of corruption and the legal gap against corrupt actors. The findings show that the most basic factor that causes the law not to run as it should is because the existing law enforcement officials have not realized the existing value of their profession as law enforcement officials, thus causing interference in law enforcement, in addition, the public is less aware of the importance of obeying the existing law. Then there is be.